Analisis Kinerja Teknis Supply Chain Batubara dari Front Pit TSBC Menuju Stockpile pada PT. Bukit Asam Tbk - M. Fawwaz Luthfi Ramadhan; Eddy Ibrahim; David Bahrain (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study analyzes the effectiveness of the coal supply chain as a key factor in maintaining production continuity and distribution stability in the mining industry. The research aims to evaluate the technical performance of the coal supply chain system at Pit TSBC of PT Bukit Asam Tbk, which integrates a shovel–truck system and a Bucket Wheel Excavator (BWE) system. The research methods include productivity analysis of loading and hauling equipment, cycle time evaluation, match factor calculation, availability assessment, and identification of potential system bottlenecks. The results indicate that the productivity of the shovel–truck system, at 3,075 tons per hour, remains below the effective capacity of the BWE system at 3,150 tons per hour, making the shovel–truck system the bottleneck of the supply chain. The average dump truck cycle time of 15.24 minutes produces 102.5 tons per hour per unit; however, an increase in hauling time to 20.82 minutes reduces productivity to 76.92 tons per hour per unit. Equipment availability, ranging from 80–90%, also significantly affects production continuity. Optimization of the match factor and improvement of hauling road infrastructure are identified as the primary recommendations to enhance overall supply chain performance.